Identification of candidate biomarkers and pathways associated with vedolizumab response in T cell populations of IBD patients by WGCNA: Hub genes associated with vedolizumab response in IBD patients - Oumeddour, Abdelkader (Cellular and Molecular Biology, 2025)
Vedolizumab is a monoclonal IgG1 antibody that prevents T cells from migrating to the gut mucosa. The purpose of this study was to identify key genes with promising therapeutic targets, and molecular pathways associated with vedolizumab response. Gene expression profiles of the GSE234736 dataset were downloaded from the Gene Expression Omnibus (GEO). A co-expression network was constructed, and significant modules were identified using the weighted gene co-expression network analysis (WGCNA) package. Next, functional enrichment analysis was performed using the R package clusterProfiler to explore gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Then, protein-protein interaction (PPI) was constructed by using the function “exportNetworkToCytoscape” and visualized by Cytoscape software. There were three modules correlated with vedolizumab response: black (r=0.41; P<4e-05), magenta (r=0.3; P<0.004), and blue (cor = -0.29, P< 0.004). Genes in selected modules were mainly enriched in lymphocyte differentiation, cytoplasmic translation, and rRNA metabolic processes, respectively. KEGG pathway analysis showed that these genes were particularly enriched in Human T-cell leukemia virus 1 infection and protein processing in the endoplasmic reticulum. Furthermore, six selected hub genes were detected in each module by overlapping PPI and WGCNA networks. Finally, GO enrichment re-analysis of selected hub genes revealed 11 hub genes that were significantly enriched in the positive regulation of intracellular protein transport and regulation of alternative mRNA splicing. This study identified hub target genes and functional pathways that may provide new insights into responsiveness to vedolizumab, a targeted therapy for IBD.